Calcium Signaling by STIM and Orai: Intimate Coupling Details Revealed - Wang, Youjun (2010)
STIM (stromal interaction molecule) and Orai, two recently identified protein families, mediate cellular Ca(2+) signals through a remarkably dynamic interaction. STIM proteins are sensors of Ca(2+) stored within the endoplasmic reticulum (ER). Orai proteins are highly selective plasma membrane (PM) channels that allow only Ca(2+) ions to flow into cells. Although present in separate membranes, the two proteins undergo profound reorganization culminating in an exquisite pas de deux within small junctional regions between the ER and PM. Before these proteins can embrace, STIM undergoes an activation process triggered by depletion of Ca(2+) stores. During its union with Orai, STIM induces the channel pore within Orai to open, allowing Ca(2+) ions to flow through the PM and provide crucial intracellular signals. Recent studies on the activation of STIM and its coupling to Orai provide valuable new insights into the nature of the liaison between these two proteins and the intricate mechanism through which activation of Ca(2+) signals occurs.